Non-randomised comparison of acute and long-term outcomes of robotic versus manual ventricular tachycardia ablation in a single centre ischemic cohort. - Luther,V; Jamil-Copley,S; Koa-Wing,M; Shun-Shin,M; Hayat,S; Linton,NW; Lim,PB; Whinnett,Z; Wright,IJ; Lefroy,D; Peters,NS; Davies,DW; et al. (Journal of Interventional Cardiac Electrophysiology, 2015)
INTRODUCTION: Robotically guided radiofrequency (RF) ablation offers greater catheter stability that may improve lesion depth. We performed a non-randomised comparison of patients undergoing ventricular tachycardia (VT) ablation either manually or robotically using the Hansen Sensei system for recurrent implantable defibrillator (ICD) therapy. METHODS: Patients with infarct-related scar underwent VT ablation using the Hansen system to assess feasibility compared with patients undergoing manual VT ablation during a similar time period. Power delivery during robotic ablation was restricted to 30 W at 60 s. VT inducibility was checked at the end of the procedure. Pre-ablation ICD therapy burdens over 6 months were compared with post-ablation therapy averaged to a 6-month period. RESULTS: Twelve consecutive patients who underwent robotic VT ablation were compared to 12 consecutive patients undergoing a manual ablation. Patient demographics and comorbidities were similar in the two groups. A higher proportion of robotic cases were urgent (9/12 (75 %)) vs. manual (4/12 (33 %)) (p = 0.1). Post-ablation VT stimulation did not induce clinical VT in 11/12 (92 %) in each group. There were no peri-procedural complications related to ablation delivery. Patients were followed up for approximately 2 years. Averaged over 6 months, robotic ICD therapy burdens fell from 32 (5-400) events to 2.5 (0-11) (p = 0.015). Therapy burden fell from 14 (10-25) to 1 (0-5) (p = 0.023) in the manual group. There was no difference in long-term outcome (p = 0.60) and mortality (4/12 (33 %), p = 1.0). CONCLUSION: Robotically guided VT ablation is both feasible and safe when compared to manual ablation with good acute and long-term outcomes.